Can Ki67 immunostaining predict response to radiotherapy in oral squamous cell carcinoma?. Issue 2 (February 1994) - Valente, G; Orecchia, R; Gandolfo, S; Arnaudo, M; Ragona, R; Kerim, S; Palestro, G
Abstract : AIMS–To determine whether immunohistochemical evaluation of the abatement of proliferating cells after a first course of radiotherapy could predict the final response to treatment in oral squamous cell carcinoma (SCC). METHODS–Frozen sections from 31 cases of histologically confirmed oral SCC were stained with the monoclonal antibody Ki67 at diagnosis and after 10 Gy of radiotherapy. The percentage difference of Ki67 positive cells among the biopsy specimens taken at the beginning and after 10 Gy was correlated with the clinical response obtained at the end of the treatment and its significance determined. RESULTS–The percentage of Ki67 positive cells at diagnosis had no significant correlation with the final therapeutic result of radiotherapy. By contrast, the 32% difference of proliferating cells after 10 Gy of radiotherapy significantly differentiated responders from non-responders (p < 0.05). Furthermore, the abatement of the growth fraction after 10 Gy of radiotherapy was significantly correlated with the complete response (p < 0.01). CONCLUSIONS–These data show that the immunohistochemical evaluation of the abatement of Ki67 positive cells after 10 Gy of radiotherapy provides an independent variable of responsiveness to radiotherapy, allowing a reliable prediction of the final therapeutic result to be made.